Automatic resonance tuning mechanism for ultra-wide bandwidth mechanical energy harvesting. (November 2020) - Shin, Youn-Hwan; Choi, Jaehoon; Kim, Seong Jin; Kim, Sangtae; Maurya, Deepam; Sung, Tae-Hyun; Priya, Shashank; Kang, Chong-Yun; Song, Hyun-Cheol
Abstract: Piezoelectric energy harvesters typically exhibit sharp peak in output power around resonance frequency (small bandwidth), which presents complexity in harvesting ambient vibrations that normally comprise of multiple frequencies. Prior attempts in designing energy harvesters with broadband response have met with practical challenges in terms of low output power, large mass and weight, and small improvements in bandwidth. Here, we report a breakthrough in demonstrating ultra-wide bandwidth piezoelectric energy harvesters through the automatic resonance tuning (ART) phenomenon. ART provides energy harvester ability to adjust its natural frequency in conjunction with ambient vibration without human intervention or additional tuning energy. The ART energy harvester utilizes the motion of the mobile proof mass in a doubly clamped oscillating beam structure to modulate the natural frequency of the beam. Detailed investigations are conducted in providing a fundamental understanding of the operation mechanism of the ART harvester by invoking beam dynamics over a wide range of vibration conditions. It is shown that bandwidth of the ART harvester (36 Hz) is 1400% larger compared to the fixed resonance energy harvester. The practical feasibility of the ART mechanism is demonstrated by evaluating the performance of the harvester mounted on a rotary pump. The results demonstrate that ART mechanism can provide the much-needed breakthrough in the deployment of mechanical energy harvesters for naturally occurring vibrations. Graphical abstract: Image 1 Highlights: Ultra-wide bandwidth piezoelectric energy harvester is demonstrated through the automatic resonance tuning (ART) phenomenon. A fundamental understanding of the operation mechanism of the ART harvester is provided by invoking beam dynamics over a wide range of vibration conditions. The bandwidth of the ART harvester (36 Hz) is 1400% larger compared to the fixed resonance energy harvester. The practical feasibility is demonstrated by evaluating the performance of the ART energy harvester mounted on a rotary pump.